PENGARUH REPUTASI AUDITOR, REPUTASI UNDERWRITER, DAN INVESTOR INSTITUSI TERHADAP UNDERPRICING: STRUDI KASUS PADA PERUSAHAAN YANG IPO DI BEI 2016-2020 - Saefudin, Saefudin (Bajang Institute, 2024)
This study aims to analyze the effect of share allocation to institutional investors, auditor reputation, and underwriter reputation on the level of underpricing in initial public offerings (IPOs) on the Indonesia Stock Exchange during the period 2016–2020. Using a purposive sampling method, this study analyzed 120 companies conducting IPOs. Data were analyzed using multiple linear regression to test the relationship between independent variables and the level of underpricing. The results showed that share allocation to institutional investors had a significant negative effect on the level of underpricing, indicating that institutional investor participation can reduce information asymmetry. In addition, auditor reputation had no effect on underpricing, while underwriter reputation showed a significant negative effect on the level of underpricing, meaning that the presence of highly reputable parties can increase market confidence in companies conducting IPOs. Control factors, such as company size and company age, also affect the level of underpricing although their contribution is relatively smaller compared to the main variables.